Quantitative Seismic Interpretation for Characterizing Carbonate Diagenesis - an Elk/Antelope Gas Field Study - Goldberg, A.; Wilson, Moyra; Sioni, S. (CSIRO Publishing, 2010)
The Elk/Antelope gas field is hosted in Miocene reefal and deepwater carbonates in Papua New Guinea. The carbonates exhibit multiple diagenetic overprints and complex internal seismic reflector heterogeneity. The objective of this study is to identify the main cause(s) of seismic reflectors within the Elk/Antelope gas field and to ascertain if diagenetic boundaries are resolvable in seismic data. Wireline logs in the Antelope-1 and Antelope-2 wellswere corrected and P-Impedance logs were generated. Wireline logs were correlated with thin section petrological studies to characterize lithological facies and diagenetic overprint. A well to 2D seismic tie for the Antelope-1 well was generated and forward modelling of synthetic seismic was conducted at the Antelope-2 well. We find that the dominant control on seismic reflection events within the reservoir are porosity variations. Lithological variations due to diagenetic overprint exert a secondary influence. Within the reservoir at the Antelope-1 well, chronostratigraphic boundaries are associated with the highest amplitude seismic reflection events. At the Antelope-2 well we model two prominent reflectors below the top carbonate event and we interpret these events to be related to diagenetically controlled porosity variation.